Assessing the ReCODE (Reading, Connecting, Observing, Discussing, and Evaluating) Instructional Model with ICT Assistance: Its Effects on Collaborative Skills and Academic Resilience of Students - Saenab, Sitti; Yunus, Sitti Rahma; Saleh, Andi Rahmat; Wulandari, -; Muhiddin, Nurhayani H. (JOIV : International Journal on Informatics Visualization, 2025)
Education in the 21st century requires students to have collaborative skills. Academic resilience is essential for facing various challenges in education. However, several studies have shown that students' collaborative skills and academic resilience are still low. This study aims to determine the effect of the ICT-assisted ReCODE instructional model on students' collaborative skills and academic resilience. This study is a quasi-experimental study with a posttest-only non-equivalent Control Group design. The population in this study consisted of all students in class VIII at SMPN 18 Makassar. The sample in this study was selected using a purposive sampling technique consisting of an experimental class and a control class. The data obtained were analyzed using descriptive and inferential statistics, including an independent t-test with a significance level of 0.05. The results of the inferential statistical analysis of collaborative skills obtained tcount = 1.75 > ttable = 1.67, which means H0 is rejected and H1 is accepted. The inferential statistical analysis of academic resilience yielded tcount = 2.04 > ttable = 1.67, indicating that H0 is rejected and H1 is accepted. Based on this analysis, it can be concluded that the ICT-assisted ReCODE instructional model affects the collaborative skills and academic resilience of class VIII students at SMPN 18 Makassar in the primary material on the human digestive system. The implications of this study suggest the need for further research on the broader application of the ICT-assisted ReCODE learning model to enhance students' collaborative skills and academic resilience.